2007
DOI: 10.2193/2006-060
|View full text |Cite
|
Sign up to set email alerts
|

Northern Bobwhites and Postfire Succession

Abstract: Our study evaluated the effects of prescribed fire on northern bobwhites (Colinus virginianus) occupying native rangelands in Rolling Plains of Texas, USA, during 2002 and 2003. Prescribed fires were conducted during February of 1996, 1998, and 2000; pastures with no recent treatment history served as controls. We quantified bobwhite densities from line transects using distance sampling. We used a repeated‐measures analysis of variance to test for treatment‐year differences in bobwhite densities. We measured p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…However, prescribed fire affected bobwhite space use of coveys which was driven by smaller home range sizes in 25-6 ' TSF which has also been identified as the time period associated with the recovery (i.e., within 2-4 growing seasons) of shinnery oak to pre-fire structure (McIlvain 1954, Harrell et al 2001. Overall, the minimal effects of fire on bobwhite behavior that we observed are similar to the observations of Ransom and Schulz (2007) who found that fire had little influence on bobwhite density in Texas.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…However, prescribed fire affected bobwhite space use of coveys which was driven by smaller home range sizes in 25-6 ' TSF which has also been identified as the time period associated with the recovery (i.e., within 2-4 growing seasons) of shinnery oak to pre-fire structure (McIlvain 1954, Harrell et al 2001. Overall, the minimal effects of fire on bobwhite behavior that we observed are similar to the observations of Ransom and Schulz (2007) who found that fire had little influence on bobwhite density in Texas.…”
Section: Discussionsupporting
confidence: 81%
“…It is well understood that the long term conservation of rangelands, as well as the species that inhabit them, can be achieved partly through the use of prescribed fire to prevent the encroachment of woody species Engle 2004, Engle et al 2008). However, uncertainty regarding the usefulness of prescribed fire for both reducing woody encroachment and promoting bobwhite habitat has been a long-standing question and management concern in the western fringe of the bobwhite distribution (Renwald et al 1978, Carter et al 2002, Ransom and Schulz 2007. Our findings shows that prescribed fire applied at a landscape scale had limited influence on short-term bobwhite behavior and space use in a shinnery oak system.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…However, differences between used and random locations also existed in the untreated pasture (LC1, Fig. 2B), suggesting that habitat structure on the WER may be generally inadequate and that our management practices may have had a neutral effect; bobwhite densities were low across these and other treatment pastures on the WER (Ransom and Schulz 2007).…”
Section: Discussionmentioning
confidence: 99%